Extragonadal germ cell tumors. A 14-year Toronto experience - Paul E. Goss; Lynn Schwertfeger; Martin E. Blackstein; Neill Iscoe; Robert J. Ginsberg; W. J. Simpson; Donald P. Jones; Frances A. Shepherd (1994)
Extragonadal germ cell tumors (EGCT) represent only 2-5% of adult germ cell malignancies. Because they are rare and biologically distinct from testis cancer, their natural history and optimal management continue to be defined. The clinical characteristics, treatment, and outcome of 40 patients are presented here.Patients were identified through the medical records of four University of Toronto teaching hospitals. All patients were treated in specialized oncology units between 1978 and 1993.Thirty-seven males and three females age 16-54 years (median, 24 years) with primary mediastinal (n = 24), retroperitoneal (n = 7), CNS (n = 7), and widespread (n = 2) EGCT were identified. Eight of nine patients (88%) with mediastinal seminoma are alive with no evidence of disease (NED) at 4-132 months (median, 45 months). After combined modality therapy, only 8 of 15 patients (53%) with mediastinal nonseminomas achieved complete remission (CR); 1 experienced relapse and died, resulting in 7 of 15 patients (47%) with NED at 45-86 months (median, 70 months). All three patients with retroperitoneal seminomas achieved CR and all have NED at 77, 103, and 120 months, respectively. Two of four patients with retroperitoneal nonseminomas have died, and the other two are alive at 36 and 54 months. Seven patients with CNS germinomas (seminoma) achieved CR after craniospinal radiation therapy, but one subsequently died after local relapse. The overall survival rate was 87% (median, 74 months). One patient with widespread choriocarcinoma died and the other achieved CR.Regardless of site of presentation, extragonadal seminomas have a greater than 80% 5-year disease-free survival rate. Mediastinal nonseminomas are biologically distinct, with a poorer prognosis. Treated with cisplatin-based chemotherapy followed by aggressive resection, approximately 50% of patients survive. CNS seminomas have a good prognosis. Nonseminomas of the CNS are extremely rare and were not represented in the current series. These findings concur with other reported series.